Implementation of the Primasi Application-Based Management Information System to Support the Quality of Educational Services at the Prima Swarga Bara Education Foundation, East Kutai Regency - Faizah Nurbani Wisnu Putri; Mada Sutapa (FKIP - Universitas Riau, 2026)
This study aims to analyze the implementation of the PRIMASI application-based management information system in supporting the quality of educational services within the Prima Swarga Bara Education Foundation and to identify the supporting factors and constraints in its implementation. The study employs a qualitative descriptive approach and was conducted at the foundation in East Kutai Regency, covering educational levels from kindergarten to junior high school as well as the foundation office. Research subjects included foundation administrators, school principals, teachers, and educational staff. Data were collected through in-depth interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing with triangulation to ensure validity. The findings reveal that the PRIMASI application has been implemented as the main system for managing educational administration, contributing to improved efficiency, data accuracy, integration, and transparency of services. Supporting factors include institutional policies, management commitment, IT support, training, and device availability. Meanwhile, constraints involve network issues, system stability, user adaptation, and discipline in data entry. The study recommends strengthening infrastructure and enhancing user support for sustainability.